New Cell Surface Protein Involved in Biofilm Formation by Streptococcus parasanguinis - Liang, Xiaobo (American Society for Microbiology, 2011)

(untitled)
Dental biofilm formation is critical for maintaining the healthy microbial ecology of the oral cavity. Streptococci are predominant bacterial species in the oral cavity and play important roles in the initiation of plaque formation. In this study, we identified a new cell surface protein, BapA1, from Streptococcus parasanguinis FW213 and determined that BapA1 is critical for biofilm formation. Sequence analysis revealed that BapA1 possesses a typical cell wall-sorting signal for cell surface-anchored proteins from Gram-positive bacteria. No functional orthologue was reported in other streptococci. BapA1 possesses nine putative pilin isopeptide linker domains which are crucial for pilus assembly in a number of Gram-positive bacteria. Deletion of the 3′ portion of bapA1 generated a mutant that lacks surface-anchored BapA1 and abolishes formation of short fibrils on the cell surface. The mutant failed to form biofilms and exhibited reduced adherence to an in vitro tooth model. The BapA1 deficiency also inhibited bacterial autoaggregation. The N-terminal muramidase-released-protein-like domain mediated BapA1-BapA1 interactions, suggesting that BapA1-mediated cell-cell interactions are important for bacterial autoaggregation and biofilm formation. Furthermore, the BapA1-mediated bacterial adhesion and biofilm formation are independent of a fimbria-associated serine-rich repeat adhesin, Fap1, demonstrating that BapA1 is a new streptococcal adhesin.